Textile art and gender: a mapping of global textile productions in the book Unraveling Women’s Art (Palíndromo, 2023)
How to sew the history of textile arts with gender issues? In the book Unravelling Women's Art: Creators, Rebels & Innovators in Textile Arts, by British art historian PL Henderson, global textile productions are explored within a gender perspective, in a mapping of productions, movements, initiatives and artists. From a curatorial involvement in a project to map artists on social media, the author built the publication from a compilation perspective, dividing the chapters by relevant topics within historical and contemporary textile productions. Distancing itself from a universal approach, neither exclusivist nor segregationist, the relationship between textiles and gender was established based on a historical analysis of the practice, often culturally associated with women in different global contexts. Despite the focus on hegemonic nations, there is an apparent desire to explore these productions in different sociocultural contexts, such as indigenous peoples and countries in the global south, for instance. In this way, the book explores productions, perspectives and possibilities in the textile arts produced by women, both in the field of visual arts and, at times, outside of it.
Keywords: textile art; women artists; art history